Branching fractions for χcJ→pp̄π0, pp̄η, and pp̄ω - Onyisi, P; Rosner, J; Alexander, J; Cassel, D; Das, S; Ehrlich, R; Fields, L; Gibbons, L; Gray, S; Hartill, D; Heltsley, B; Hunt, J; et al. (2010)
Using a sample of 25.9×106 ψ(2S) decays acquired with the CLEO-c detector at the CESR e+e- collider, we report branching fractions for the decays χcJ→pp̄π0, pp̄η, and pp̄ω, with J=0, 1, 2. Our results for B(χcJ→pp̄π0) and B(χcJ→pp̄η) are consistent with, but more precise than, previous measurements. Furthermore, we include the first measurement of B(χcJ→pp̄ω). © 2010 The American Physical Society.